2019
DOI: 10.3390/ijms20215259
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Proteins Play Critical Roles in Plant Adaptation to Phosphorus Deficiency

Abstract: Phosphorus is one of the mineral nutrient elements essential for plant growth and development. Low phosphate (Pi) availability in soils adversely affects crop production. To cope with low P stress, remodeling of root morphology and architecture is generally observed in plants, which must be accompanied by root cell wall modifications. It has been documented that cell wall proteins (CWPs) play critical roles in shaping cell walls, transmitting signals, and protecting cells against environmental stresses. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 123 publications
0
16
0
Order By: Relevance
“…Recently, Zhang and colleagues reported that the anac044 mutant exhibits insensitivity to Pi deficiency by elevating Pi reutilization of the cell wall (Zhang et al., 2021), which functions as an important Pi pool when plants encounter Pi deficiency (Wu et al., 2019; Zhu et al., 2015). In the anac044 mutant, there is more soluble Pi available through its remobilization from the cell wall.…”
Section: Ddr To Environmental Stimulimentioning
confidence: 99%
“…Recently, Zhang and colleagues reported that the anac044 mutant exhibits insensitivity to Pi deficiency by elevating Pi reutilization of the cell wall (Zhang et al., 2021), which functions as an important Pi pool when plants encounter Pi deficiency (Wu et al., 2019; Zhu et al., 2015). In the anac044 mutant, there is more soluble Pi available through its remobilization from the cell wall.…”
Section: Ddr To Environmental Stimulimentioning
confidence: 99%
“…Overexpressing GmPAP1-like enhanced Arabidopsis growth and P content when dNTP was supplied as the sole external P source [ 25 ]. In addition, some DAPs functions in cell wall carbohydrate metabolism were also identified to be up-regulated in Arabidopsis suspension cells or root cell walls under P-deficient conditions, such as polygalacturonase (PG) and xyloglucan endotransglycosylase (XET), which was suggested to release cell wall-bound Pi under low-P conditions [ 25 , 112 , 114 ]. Additionally, since changes in polysaccharides in cell wall metabolism could influence the rhizosphere size, which was suggested to be positively correlated with P accumulation in plants, DAPs related to cell wall metabolism might affect plant P efficiency partially through changing rhizosphere size [ 115 ].…”
Section: Daps Reveal Complex Repones Of Plants To P Deficiencymentioning
confidence: 99%
“…We can also see a slight difference in the expression of the berberine bridge enzyme (BBE) between heat and drought. It was reported that BBE is highly important in plant adaptation to phosphorus deficiency [58], which is more related to drought [59].…”
Section: Alsamman Et Al 2021mentioning
confidence: 99%